Pengaruh Self-Control Stres Kerja dan Karakteristik Pekerjaan Terhadap Cyberloafing di Bank BPR Cirebon - Permana, Hudaya Galuh; Nugraha, Enggun Yoga; Lorenza, Nida Silvia; Pamuji, Rita Sri Silvia (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
This research aims to examine the influence of self-control, work stress, and job characteristics on cyberloafing at BPR Cirebon Bank. This study was conducted using a descriptive method with a quantitative approach. The population of this study is all employees of BPR Cirebon Bank, totaling 98 people. The sampling technique employed is non-probability sampling or saturated sampling, resulting in a sample size of 98 individuals, which means all employees of BPR Cirebon Bank. Data collection was conducted using a questionnaire with a Likert scale. Data analysis used multiple linear regression analysis. The results of this study show that self-control, work stress and job characteristics have a simultaneous and significant effect on cyberloafing. Self-control has a negative and significant influence on cyberloafing. Job stress has a positive and significant influence on cyberloafing. Job characteristics have a positive and significant effect on cyberloafing